The class and finely analytic functions. (August 2018) - Sadullaev, A.; Ibragimov, Z.
Abstract: The paper is concerned with the class of holomorphic functions introduced by Gonchar, and the class, which is a special case of the former. A holomorphic function in a neighbourhood of belongs to, if it admits rapid rational approximation in some closed ball, . It is proved that in certain cases functions in the class are finely analytic in the whole of . Bibliography: 26 titles.